2011
DOI: 10.1177/1059601110391251
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Team Performance in a Highly Competitive Environment

Abstract: In this article, we empirically validate a version of the input-mediator-output-input (IMOI) model (Ilgen, Hollenbeck, Johnson, Jundt, 2005), adapting it to investigate virtual team performance in a highly competitive environment. Our hypotheses are tested using structural equation modeling across time periods with data obtained from 606 professional online gaming teams belonging to the European Electronic Sports League. The findings validate the hypothesized IMOI model, and demonstrate the effects of anticipa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 85 publications
0
48
0
2
Order By: Relevance
“…(Algesheimer et al, 2011 did not clearly delineate the effectiveness and the performance in GVTs. Based on the previous applications for two terms in the relevant literature, we would contend that these words cannot be utilised interchangeably.…”
Section: Gvts Effectiveness/performancementioning
confidence: 92%
See 1 more Smart Citation
“…(Algesheimer et al, 2011 did not clearly delineate the effectiveness and the performance in GVTs. Based on the previous applications for two terms in the relevant literature, we would contend that these words cannot be utilised interchangeably.…”
Section: Gvts Effectiveness/performancementioning
confidence: 92%
“…As a result, voluminous amount of relevant studies are available in the field, as a broad literature review from 2007 identified around 130 team performance models and frameworks (Salas et al, 2007). Nevertheless, the body of knowledge on the variables contributing to the performance of GVTs and the factors determining their effectiveness suffers from paucity of research (Algesheimer et al, 2011, Ebrahim et al, 2009. Researchers have acknowledged the great effects of variables related to social matters (Peters & Karren, 2009, Lin et al, 2008, task-related variables (Lipnack and Stamps, 2000), and the quality of communications (Maznevski & Chudoba, 2000, Ahn et al, 2005 on the effectiveness of GVTs.…”
Section: Gvts Effectiveness/performancementioning
confidence: 99%
“…Consequently, the outcomes and impacts are difficult to replicate outside the context where it was evaluated. A review of literature suggests that relatively little is known about the elements that determine and influence virtual team performance (Lee-Kelley & Sankey, 2008;Algesheimer et al, 2011). This has led to the need for a greater understanding of factors influencing multidisciplinary virtual team interaction and collaboration (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Despite extensive research conducted to understand how and why teams achieve desired outcomes, relatively little is known about the elements that determine and influence virtual team performance (Lee-Kelley & Sankey, 2008;Algesheimer et al, 2011). Gaudes et al (2007) compiled a comprehensive list of factors that contribute towards the effectiveness of virtual teams, and grouped them against an inputs-processes-outputs model and facets of individual, team, leader, organisation, project, and technology.…”
Section: The Challenges Of Communication In a Distributed Teammentioning
confidence: 99%
“…Second, under team development competition, team members feel a strong sense of a common goal (Algesheimer et al, 2011;Bosch-Sijtsema et al, 2011;Chen et al, 2006;Mehta et al, 2009;Tjosvold et al, 2004), which in turn enhances their intention of positively influencing the team. Prior research shows that interpersonal competition could enhance intrinsic motivation (Abuhamdeh and Csikszentmihalyi, 2009;Tauer and Harackiewicz, 2004).…”
Section: Within-team Competition and Team Empowermentmentioning
confidence: 99%